Penerapan Teknologi Ramah Lingkungan di Perusahaan PT. Toba Pulp Lestari, Tbk untuk Edukasi Masyarakat - Mutiara S. Simanjuntak; Juanto Simangunsong (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
The Community Service Program aims to increase awareness and knowledge among the community and students about the importance of environmentally friendly technology and to encourage active participation in environmental conservation. Through literature studies, field observations, interviews, and campaigns, this activity has achieved several important results.The results of the activities showed a significant increase in awareness and knowledge about environmentally friendly technologies implemented by PT. Toba Pulp Lestari, Tbk, including liquid and solid waste management, renewable energy utilization, and sustainable forest management. The company's support and commitment to the application of environmentally friendly technology and community education programs have driven the initiation of environmental conservation efforts, ensuring the sustainability of these programs.Based on the results of the activities, policy recommendations were prepared and submitted to PT. Toba Pulp Lestari, Tbk, and other related parties to enhance the implementation of environmentally friendly technology and strengthen community education programs in the future. This Community Service Program demonstrates that collaboration between the company and the community can produce significant positive impacts on environmental conservation and long-term sustainability.